2017
DOI: 10.1007/s00330-017-4864-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyvinyl alcohol copolymer with detachable balloons for the embolisation of direct carotid cavernous fistula: a single-centre experience

Abstract: • Carotid-cavernous fistula results from a damaged carotid artery. • Detachable balloons have been used with success for many years. • Some reported excellent outcomes after embolisation with polyvinyl alcohol copolymer. • Treatment expense is much higher in the polyvinyl alcohol copolymer group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…After direct comparison with other techniques widely used in literature for CCF occlusion, FDDs in combination with other embolizing materials offer a lower immediate occlusion rate, but comparable if not better long-term occlusion rates and clinical improvement. 3135 Arifin et al. presented a case series with 100% immediate occlusion rate of CS coiling, while embolization using detachable balloons was 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After direct comparison with other techniques widely used in literature for CCF occlusion, FDDs in combination with other embolizing materials offer a lower immediate occlusion rate, but comparable if not better long-term occlusion rates and clinical improvement. 3135 Arifin et al. presented a case series with 100% immediate occlusion rate of CS coiling, while embolization using detachable balloons was 40%.…”
Section: Discussionmentioning
confidence: 99%
“…reported that in 105 cases of CCFs treated with detachable balloon or polyvinyl alcohol copolymer, occlusion rates ware 96,5% and 84,2% respectively, but with some major complications, including death. 35 Moreover, Ertl et al. using a combination of endovascular techniques without FDD, reported a complication rate of 8% and long-term follow up occlusion rate of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…From the economical perspective, detachable balloons are much cheaper than coils combined with liquid embolism in china with comparable complete occlusion rate and recanalization rate [ 21 ]. Others reported a higher recanalization rate of detachable balloons [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, several cases are described where glue, onyx, or polyvinyl alcohol (PVA) particles were used by the interventionist in combination with detachable coils to adequately pack the fistula with variable results. 17 18 Using liquid/particle embolizing agents for these high-flow conditions carry a high-complication rate like nontarget embolization of cortical veins or an arterial embolic stroke. 17 18 We did not use liquid or particle agents for direct CCF embolization in any of our cases.…”
Section: Discussionmentioning
confidence: 99%